Existential distress among healthcare providers caring for patients at the end of life. Issue 1 (March 2015) - Pessin, Hayley; Fenn, Natalie; Hendriksen, Ellen; DeRosa, Antonio P.; Applebaum, Allison
Abstract : Purpose of review: Existential distress is well documented among patients at end of life (EOL) and increasingly recognized among informal caregivers. However, less information is known about existential concerns among healthcare providers working with patients at EOL, and the impact that such concerns may have on professionals. Recent findings: Recent literature documents five key existential themes for professionals working in EOL care: (1) opportunity for introspection; (2) death anxiety and potential to compromise patient care; (3) risk factors and negative impact of existential distress; (4) positive effects such as enhanced meaning and personal growth; and (5) the importance of interventions and self-care. Summary: EOL work can be taxing, yet also highly rewarding. It is critical for healthcare providers to make time for reflection and prioritize self-care in order to effectively cope with the emotional, physical, and existential demands that EOL care precipitates.